Do Herbal Medicines Promote Weight loss? (https://doi.org/10.1111/dom.13973) (Diabetes, Obesity and Metabolism Now, 2023)
AIMS: To establish age- and sex-specific reference percentiles for body shape indices in Chinese adults and to develop a composite body shape index (CBSI) for age-related chronic diseases screening. MATERIALS AND METHODS: From the China National Health Survey, we recruited adults across six provinces from 2023 to 2025. Sex- and age-specific percentile curves for body shape indicators were constructed using the Lambda-Mu-Sigma method. CBSI was derived by sex-stratified exploratory factor analysis with varimax rotation, integrating adiposity, muscle function, and body proportion. Associations with chronic diseases were assessed in a training population (n = 11 220) and validated in an independent population (n = 5745). Incremental value over BMI was evaluated by integrated discrimination improvement (IDI) and net reclassification improvement (NRI). RESULTS: Body shape index trajectories differed substantially by sex. Compared with CBSI < -0.5, CBSI > 0.5 was associated with elevated odds of hypertension (OR 6.42, 95% CI 5.51-7.48), diabetes (2.76, 2.25-3.38), dyslipidemia (3.86, 3.37-4.41), hyperuricemia (5.44, 4.67-6.34), abnormal ECG (1.63, 1.24-2.13), coronary heart disease (2.31, 1.62-3.27), stroke (3.05, 1.95-4.78), chronic kidney disease (3.06, 1.79-5.23), and musculoskeletal disorders (1.67, 1.09-2.55). These associations persisted in the validation set and individuals aged > 60 years. Adding CBSI to BMI-based models improved disease identification, with positive IDI and category-free NRI. CONCLUSIONS: Age- and sex-specific reference centiles for body shape indicators can reflect trajectories of body composition and muscle health across the lifespan, which facilitates sarcopenia screening. The CBSI serves as an integrated screening tool for high-risk populations.